Sex-Specific Anxiety and Prefrontal Cortex Glutamatergic Dysregulation Are Long-Term Consequences of Pre-and Postnatal Exposure to Hypercaloric Diet in a Rat Model. - Rivera-González, Patricia; Tovar, Rubén; Ramirez-Lopez, Maria Teresa; Navarro, Juan Antonio; Vargas, Antonio; Suárez-Pérez, Juan; Rodriguez de Fonseca, Fernando (MDPI, 2020)
Both maternal and early life malnutrition can cause long-term behavioral changes in the offspring, which depends on the caloric availability and the timing of the exposure. Here we investigated in a rat model whether a high-caloric palatable diet given to the mother and/or to the offspring during the perinatal and/or postnatal period might dysregulate emotional behavior and prefrontal cortex function in the offspring at adult age. To this end, we examined both anxiety responses and the mRNA/protein expression of glutamatergic, GABAergic and endocannabinoid signaling pathways in the prefrontal cortex of adult offspring. Male animals born from mothers fed the palatable diet, and who continued with this diet after weaning, exhibited anxiety associated with an overexpression of the mRNA of Grin1, Gria1 and Grm5 glutamate receptors in the prefrontal cortex. In addition, these animals had a reduced expression of the endocannabinoid system, the main inhibitory retrograde input to glutamate synapses, reflected in a decrease of the Cnr1 receptor and the Nape-pld enzyme. In conclusion, a hypercaloric maternal diet induces sex-dependent anxiety, associated with alterations in both glutamatergic and cannabinoid signaling in the prefrontal cortex, which are accentuated with the continuation of the palatable diet during the life of the offspring.
Keywords: Corteza prefrontal; Enfermedades mentales - Aspectos nutricionales; Perinatología; Diferencias sexuales; Modelos animales en investigación; endocannabinoid system; perinatal programming; prefrontal cortex.; endocannabinoid system; perinatal programming; prefrontal cortex.; endocannabinoid system; perinatal programming; prefrontal cortex.